INVESTIGATION OF FAILURE TRADING PRACTICES IN SPORTS ACTIVITY - V. Dimitrov (Trakia Journal of Sciences)
Sporting services are increasingly important as a means of meeting the sporting needs of citizens and are an opportunity for the development of regions, including as a means of boosting employment. Due to increased competition, new unfair practices are emerging in this area. The methods used in the survey are regulatory review, case law review, and questionnaire survey. The results present the most common unfair practices and related misleading advertisements, as well as case law analysis of such cases. In conclusion, many users are misled by such practices, to put in place a reliable system for preventing sports centers, including fitness centers, from posting false reviews and recommendations on their sites.